Trans family systems framework: Theorizing families' gender investments and divestments in cisnormativity - Brandon Andrew Robinson; Amy L. Stone (2024)
Abstract Objective This article calls on family scholars to take seriously how families are invested and divested in maintaining and reproducing cisnormativity. Background Families can be a prime institution for the reproduction of cisnormativity. For transgender and nonbinary family members, families' investment in cisnormativity can generate ambiguous and toxic familial relations. Yet, family studies have not developed an adequate framework to examine how and why cisnormativity operates within families. Method The authors engage with empirical and theoretical work on gender, intersectionality, and families to examine how cisnormativity operates within family dynamics and processes. This article also focuses on work about trans people and families to capture how cisnormative processes within families affect trans people's familial relations. Results The authors advance a trans family systems framework to show how families' cisgender investments and divestments shape familial processes. The concept of cisnormative compliance is introduced to capture the beliefs and practices of obedience established by family members for the purpose of reproducing cisnormativity. Family studies can move forward in studying these cisnormative processes through documenting how gender accountability shapes family dynamics, implementing new methods, furthering an intersectional analysis, and exploring complexities of space and place. Conclusion To reimagine gender and families, family scholars need to study and foreground how cisnormativity shapes family dynamics and processes.